On the unfairness of actuarial fair annuities - An Chen; Steven Vanduffel (Decisions in Economics and Finance, 2023)
Actuarial fairness pertains to the situation in which the price of an insurance contract is equal to its expected outcome. We show that actuarial fairness leads to "unfairness" in that annuitants with higher survival rates can choose a better payoff in the sense of second-order stochastic dominance than those with lower survival rates. To deal with this issue, we propose equal utility pricing, i.e., we determine prices such that all contracts have the same (nonlinear) utility from the viewpoint of a third party (e.g., a social planner). This approach is of particular relevance with respect to the design of group self-annuitization schemes.
Keywords: G22; J32; 330; Fairness; Actuarial pricing; Financial pricing; Equal utility